Azimuthal variations in xylem structure and water relations in cork oak (Quercus suber) - Čermák, Jan; Barij, Nadia; Stokes, Alexia (IAWA Journal, 2011)
Keywords: hydraulic conductivity; sap; vessel lumina; wood anatomy

Hydrological properties of cork container media - Carmona, E.; Ordovas, J.; Moreno, M. T.; Aviles, M.; Aguado, M. T.; Ortega, M. C. (HORTSCIENCE, 2003)
Static hydrological properties \{[\}aeration capacity; easily available water, reserve water, water release curves: theta(v)(Psi(m)), and specific humidity curves] and dynamic hydrological properties (saturated and unsaturated hydraulic conductivity) of substrates based on industrial cork residue (the bark of Quercus suber L.) and cork compost were studied. Samples of similar granulometry have been used to establish the effect of cork composting on the aforementioned physical properties. Different models were tested to describe the mechanism of water release from these materials. Van Genuchten's model (Van Genuchten, 1978) was the best fit and produced specific humidity curves that revealed slight differences in the ratio of water capacity function. When cork residues were composted for 7 months, important changes occurred in hydrological properties of the material as it became more wettable. Water retention significantly increased from 45% to 54%, at a potential of 5 kPa, although this did not necessarily result in increased water available to plants. A study of the unsaturated hydraulic conductivity (K-unsat) of these materials revealed a significant decrease in the K-unsat water potential at 0-5 kPa, which corresponds to the range in which the irrigation with these substrates was usually carried out. The long composting process resulted in increased K-unsat between 4 and 5 times that of uncomposted material, which would improve the water supply to the plant.
The following values have no corresponding Zotero field: pub-location: 113 S WEST ST, STE 200, ALEXANDRIA, VA 22314-2851 USA publisher: AMER SOC HORTICULTURAL SCIENCE
Keywords: growing media; horticultural substrate; hydraulic conductivity; physical properties; water release curves